2019
DOI: 10.1155/2019/9417498
|View full text |Cite
|
Sign up to set email alerts
|

Syzygium cumini Leaf Extract Reverts Hypertriglyceridemia via Downregulation of the Hepatic XBP-1s/PDI/MTP Axis in Monosodium L-Glutamate-Induced Obese Rats

Abstract: Syzygium cumini is used worldwide for the treatment of metabolic syndrome-associated outcomes. Previously, we described the antihypertriglyceridemic effect of the hydroethanolic extract of S. cumini leaf (HESc) in monosodium L-glutamate- (MSG-) induced obese rats. This study sought to investigate the molecular mechanisms underlying the antihypertriglyceridemic effect of HESc in MSG-obese rats. Newborn male Wistar rats were injected subcutaneously with MSG (4.0 g/kg/day, obese group) or saline 1.25% (1.0 mL/kg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…CPT1 stimulates the uptake of fat and mitochondrial fatty acid oxidation, and PPARα can regulate the β-oxidation of fatty acids by upregulating CPT1 to prevent excessive lipid accumulation in the liver . On the other hand, p-AMPK enhances fatty acid oxidation by increasing PPARα expression . MTP is a lipid transfer protein that transfers TG from hepatocytes to apolipoprotein B (ApoB) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CPT1 stimulates the uptake of fat and mitochondrial fatty acid oxidation, and PPARα can regulate the β-oxidation of fatty acids by upregulating CPT1 to prevent excessive lipid accumulation in the liver . On the other hand, p-AMPK enhances fatty acid oxidation by increasing PPARα expression . MTP is a lipid transfer protein that transfers TG from hepatocytes to apolipoprotein B (ApoB) .…”
Section: Discussionmentioning
confidence: 99%
“…47 On the other hand, p-AMPK enhances fatty acid oxidation by increasing PPARα expression. 48 MTP is a lipid transfer protein that transfers TG from hepatocytes to apolipoprotein B (ApoB). 49 Because of the increased level of p-AMPK after PP04 administration, the protein expression levels of PPARα, CPT1, and MTP were enhanced drastically (Figure 5D).…”
Section: ■ Discussionmentioning
confidence: 99%
“…ApoB100 and microsomal TG transfer protein (MTP) mediate VLDL secretion in hepatocytes. Studies have revealed that pharmacological inhibition of MTP can be used to treat hyperlipidaemia in rats with monosodium L-glutamate-induced obesity, while increases in MPT gene or protein expression can be used to treat NAFLD [33][34][35]. Studies have also indicated that upregulating PPAR-α, carnitine palmitoyltransferase-1a (CPT-1a) and fatty TG lipase (ATGL) to enhance FA oxidation and lipolysis can improve NAFLD in micee [36,37].…”
Section: Pathogenesis Of Nafld and Glycolipid Metabolismmentioning
confidence: 99%
“…Andrographolide, the main bioactive chemical constituent of A. paniculata , has been reported to have antidiabetic potential ( Yu et al., 2008 ; Zhang et al., 2009 ; Sari et al., 2015 ). S. cumini is a native Indian tree that is widespread around the world and is also used as an antidiabetic ( Chagas et al., 2018 ; França et al., 2019 ). In Indonesia, the tree is referred to as Jamblang.…”
Section: Introductionmentioning
confidence: 99%